Pompa Otomatis dan Monitoring Kekeruhan Tempat Penampungan Air: (Studi pada TPQ At – Ta’awun) - Ummi Hanik; Dani Sasmoko; Nuris Dwi Setiawan; Iman Saufik Suasana; Sulartopo Sulartopo (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to design and develop an Internet of Things (IoT)-based automatic water pump monitoring and control system. The system utilizes an ESP32 microcontroller connected to an ultrasonic sensor to measure water level and a turbidity sensor to detect water clarity. The pump is automatically activated when the water level drops below a specified threshold and deactivated when the tank is full. Furthermore, when the turbidity value exceeds a certain limit (e.g., >40 NTU), the system sends notifications to the user via the Blynk application. In addition, notifications are also sent through a Telegram bot, allowing users to receive alerts instantly without needing to open the Blynk app. Key data such as water level distance, NTU value, pump status, and water condition are displayed locally on a 16x2 LCD and remotely on the Blynk dashboard.System testing was conducted using samples of clean water, tea, and milk coffee to represent varying levels of turbidity. The results showed that the system effectively detected different turbidity levels and automatically controlled the pump based on the water level. This system offers an efficient real-time solution for monitoring water quality and can be applied in places such as Islamic schools (TPQ), educational institutions, or households.